New genus and species of Anablepidae (Teleostei, Cyprinodontiformes) from the Late Miocene of Argentina. (December 2018) - Bogan, Sergio; Contreras, Víctor H.; Agnolin, Federico; Tomassini, Rodrigo L.; Peralta, Silvio
Abstract: A new anablepid (Cyprinodontiformes) from the Late Miocene of Puchuzum locality, San Juan Province, Argentina is described here. The collected specimens include male and female individuals showing marked sexual dimorphism and represented different ontogenetic stages. The fossils show a unique combination of characters reveals a new genus and species, Sanjuanableps calingasta . The phylogenetic analysis allowed to identify a monophyletic clade including Anableps, Tucmanableps and Sanjuanableps, which constitutes the sister group of other anablepids. During the Late Miocene, Sanjuanableps possibly formed monospecific shoals in shallow ponds of salty water in semiarid environments. Highlights: The new species is represented by a large number of female and male individuals. The new species appears to be related to the genus Anableps . The finding indicates that part of the history of some anablepids is not directly related with the Paranian marine transgression.